The working environment and livestock production systems in Nigeria (2001)
Favorable and safe working conditions are important factors in animal production. In urban and peri-urban areas of Nigeria, most the livestock arc kept under the extensive System where animals are exposed lo industrial wastes, oil Spills and domestic effluents, which might leave serious effects on the health of the animals. And for a country (hat has an annual record of over a thousand oil spillages, pollution of soils often leads to destruction of pasture land and death of water animals. In its drive to increase food production, many Nigerian farmers have been using pesticides on their farms. Animals in search of forage and water are often killed when they come in contact with pesticide treated farms and contaminated water. The poisoning of sheep and goats by organochlorine residues on cocoa farms have been recorded in many parts of the country and birds have also been known to be poisoned by acaricides which are used as washes dusting powders for the treatment of fleas and lice. This paper thus describes the various deleterious effects of common pollutants on the livestock production System in Nigeria. Suggestions were also made on the ways and means of reducing exposure of animals to environmental toxicants.